Anterior‐posterior electrophysiological activity characterizes Parkinsonian visual misperceptions. Issue 4 (14th May 2021) - Muller, Alana J.; Shine, James M.; Rolle, Camarin E.; Chitty, Kate; Hall, Julie M.; Halliday, Glenda M.; Hermens, Daniel F.; Lewis, Simon J.G.; O'Callaghan, Claire
Abstract: Background: The neural mechanism underlying visual hallucinations (VH) in Parkinson's disease (PD) relates to impaired network‐level communication; however, the timing of this effect is poorly understood. Aim: To elucidate the temporal evolution of EEG signals during misperceptions in PD patients. Methods: Twenty‐seven patients with PD performed a validated behavioral task (the bistable percept paradigm, BPP) capable of eliciting visual misperceptions while being monitored using scalp electroencephalography (EEG). Using a data‐driven clustering analysis, EEG electrodes behaving similarly over time were clustered together. Misperceptions on the BPP were then related to the clustered time‐series EEG patterns. Results: Patients with PD demonstrated distinctly different EEG signals during misperceptions, highlighted by early frontal and late posterior activity. Additionally, different aspects of the electrophysiological response during misperceptions were correlated with hallucination severity. Conclusions: Our results provide evidence that VH in PD may be related to early activity in frontal regions followed by activity within posterior regions of the cortex. These results support specific predictions of hypothetical models that emphasize an imbalance in top‐down vs bottom‐up processing during misperceptions and advance our understanding of the pathophysiology of VH in PD.